2007
DOI: 10.1677/erc-07-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Mia/Cd-rap gene expression is downregulated by the high-mobility group A proteins in mouse pituitary adenomas

Abstract: The high-mobility group A (HMGA) family of proteins orchestrates the assembly of nucleoprotein structures playing important roles in gene transcription, recombination, and chromatin structure through a complex network of protein-DNA and protein-protein interactions. Recently, we have generated transgenic mice carrying wild type or truncated HMGA2 genes under the transcriptional control of the cytomegalovirus promoter. These mice developed pituitary adenomas secreting prolactin and GH mainly due to an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Among these genes, we previously focused our attention on the Mia/Cd-rap gene, whose expression was essentially suppressed in all pituitary adenomas tested by cDNA microarray. We showed that the HMGA proteins directly bind to the promoter of the Mia/Cd-rap gene and are able to down-regulate its expression (14).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Among these genes, we previously focused our attention on the Mia/Cd-rap gene, whose expression was essentially suppressed in all pituitary adenomas tested by cDNA microarray. We showed that the HMGA proteins directly bind to the promoter of the Mia/Cd-rap gene and are able to down-regulate its expression (14).…”
Section: Introductionmentioning
confidence: 96%
“…Here, we focus our attention on the ccnb2 gene, coding for the cyclin B2 protein, which showed an 8-fold change increase in the pituitary adenomas in comparison with normal pituitary glands from control mice (14). Cyclin B2 is a member of the B-type cyclin family, including B1 and B2.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have widely explored the potential mechanisms of HMGA-dependent pituitary oncogenesis, and our group has demonstrated the involvement of HMGA proteins in the positive regulation of E2F1 activity (Fedele et al, 2006) and Ccnb2 expression (De Martino et al, 2007) resulting in pituitary cell cycle dysregulation and development of pituitary adenomas. However, the so far identified cytogenetic alterations (gene amplifications, chromosome overrepresentation or formation of derivative chromosomes) affecting HMGA1 and HMGA2 loci or the chromosomes where HMGA genes are located have not been detected in all the human pituitary adenomas even though almost all of them overexpress the HMGA proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of the HMGA-mediated E2F1 activation in pituitary tumorigenesis was confirmed by crossing Hmga2-overexpressing with E2f1-knockout mice, which resulted in the suppression of pituitary tumorigenesis in double mutant mice (Fedele et al, 2006). The analysis of the expression profile of pituitary adenomas developed by Hmga transgenic mice in comparison with normal pituitary from wild-type mice led to the identification of other genes potentially down-stream in the molecular pathway leading to PA onset in Hmga transgenic mice (De Martino et al, 2007;2009). Among these genes, Mia/Cd-rap, coding for a secreted product of malignant melanoma cells, and Ccnb2, encoding the cyclin B2, which plays an important role in cell cycle progression, are directly regulated, by the HMGA proteins at transcriptional level (De Martino et al, 2007;2009).…”
Section: Hmga1 and Hmga2mentioning
confidence: 96%
“…The analysis of the expression profile of pituitary adenomas developed by Hmga transgenic mice in comparison with normal pituitary from wild-type mice led to the identification of other genes potentially down-stream in the molecular pathway leading to PA onset in Hmga transgenic mice (De Martino et al, 2007;2009). Among these genes, Mia/Cd-rap, coding for a secreted product of malignant melanoma cells, and Ccnb2, encoding the cyclin B2, which plays an important role in cell cycle progression, are directly regulated, by the HMGA proteins at transcriptional level (De Martino et al, 2007;2009). Consistent with these data, the MIA gene, which is down-regulated by HMGA proteins, is down-regulated in human prolactinomas compared to normal pituitary (Evans et al, 2008), and the CCNB2 gene, which is up-regulated by HMGAs, is over-expressed in PA versus normal pituitary, in statistically significant association with HMGA expression (De Martino et al, 2009).…”
Section: Hmga1 and Hmga2mentioning
confidence: 99%